La cattura della realtà coinvolge tutti gli operatori nell’edilizia (GEOmedia, 2022)
Teorema has been dealing for years with the offer of instruments for 3D digitization of buildings and environments, which are increasingly in demand as technological evolution advances. In this article, it is highlighted the importanceof Reality Capture in the construction world, connecting several professionals involved in the construction process.This technology allows the replication of the physical world and its transformation into a virtual environment andcan be used to monitor the progress of a project and quickly compare whether the construction follows the designplan, ensuring quality control and highlighting any problems.